Rapid Detection of Aspergillus flavus isolates producing aflatoxin using UV light on different culture media (Baghdad Science Journal, 2014)
This study included the isolation and identification of Aspergillus flavus isolates associated with imported American rice grains and local corn grains which collected from local markets, using UV light with 365 nm wave length and different media (PDA, YEA, COA, and CDA ).One hundred and seven fungal isolates were identified in rice and 147 isolates in corn.4 genera and 7 species were associated with grains, the genera were Aspergillus ,Fusarium ,Neurospora ,Penicillium . Aspergillus was dominant with occurrence of 0.47% and frequency of 11.75% in rice grains whereas in corn grains the genus Neurospora was dominant withoccurrence of 1.09% and frequency 27.25% ,results revealed that 20 isolates out of 50 A. flavus isolates were able to produce aflatoxin .results also indicated that the best medium for toxin production was (COA) followed by (PDA and YEA), whereas the suitable temperature and incubation period for toxin production was 35?c and 7 days.